2017
DOI: 10.1002/cctc.201601178
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐Mediated Synthesis of Zinc Oxide Supported Nickel‐Palladium Alloy Catalyst for the Selective Hydrogenation of 1,3‐Butadiene

Abstract: Supporting informationand the ORCID identification number(s) for the author(s) of this article can be found underh ttp://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…And properties of the support such as geometric, acidic or basic sites, and electronic and inherit surface O 2 vacancies affect its performance. In our previous work, we observed that Ni–Pd affixed on ZnO and TiO 2 with higher oxygen vacancies promoted catalytic activity compared to CuO and SiO 2 . Moreover, TiO 2 - and γ-Al 2 O 3 -supported Pt–Ni alloy catalyst presented marked results in 1,3-butadiene hydrogenation, with the former support performing lower than the latter due to structural stability caused by the dissimilar supports .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…And properties of the support such as geometric, acidic or basic sites, and electronic and inherit surface O 2 vacancies affect its performance. In our previous work, we observed that Ni–Pd affixed on ZnO and TiO 2 with higher oxygen vacancies promoted catalytic activity compared to CuO and SiO 2 . Moreover, TiO 2 - and γ-Al 2 O 3 -supported Pt–Ni alloy catalyst presented marked results in 1,3-butadiene hydrogenation, with the former support performing lower than the latter due to structural stability caused by the dissimilar supports .…”
Section: Introductionmentioning
confidence: 94%
“…Our group proposed the plant-mediated and microwave pathway to mitigate some of the challenges mentioned above. Ag, Ni, introduction of halide ions (KBr, KCl, and KI) and later self-dopant C, and N-TiO 2 were employed using the plant-mediated method to increase Pd selectivity toward butenes. ,, The recorded overall butene selectivities were above 80% in all cases and between 40 and 66% for 1-butene, which is remarkable. In addition, the reactions were conducted at temperatures ≤50 °C, making the process energy-efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, noble metals (e.g., Pd, Pt, Au, etc.) are widely used as heterogeneous catalysts due to their high catalytic performance for hydrogenation reactions [9,10]. However, noble metallic catalysts normally have low selectivity to alkenes (70%-85%) during the catalytic selective hydrogenation reaction because of their strong hydrogen activation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, noble metallic catalysts normally have low selectivity to alkenes (70%-85%) during the catalytic selective hydrogenation reaction because of their strong hydrogen activation [10][11][12]. In order to increase the selectivity to alkenes, nowadays, one of the most wildly used method is to modify the surficial property (i.e., electro density, the distribution of noble metal atom and so on) by introducing a second non-noble metal assistant, and forming noble/non-noble bimetallic catalysts, such as Pd-Ni [9], Pd-Cu [13][14][15], Pd-Co [16,17], Pd-Zn [18,19], Pt-Cu [20][21][22][23] and so on. Specifically, the Pt-Cu alloys supported on Al2O3 synthesized by Lucci et al [21] have shown 99% butenes selectivity at full conversion temperature (T100%) in selective hydrogenation of butadiene reaction.…”
Section: Introductionmentioning
confidence: 99%
“… 22,23 Natural plants usually contain abundant biomass, which can serve as both reductants and stabilizers in reducing metal ions, thus excessive employment of chemical reagents can be avoided. 18 And many plant leaves such as Cacumen platycladi , 24,25 Persimmon ( Diopyros kaki ), 26 mahogany 27 and Cinnamomum camphora 28 were all reported in assembling bimetallic alloy NPs. Nevertheless, different plants are easily subjected to region influence and unsuitable for worldwide range of promotion.…”
Section: Introductionmentioning
confidence: 99%